1992
DOI: 10.1128/aac.36.9.2014
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial prophylaxis for major head and neck surgery in cancer patients: sulbactam-ampicillin versus clindamycin-amikacin

Abstract: A total of 99 patients with head and neck cancer who were to undergo surgery were randomized in a prospective comparative study of sulbactam-ampicillin (1:2 ratio; four doses of 3 g of ampicillin and 1.5 g of sulbactam intravenously [i.v.] Wound infections occurred in 14 (33%) sulbactamampicillin-treated patients and 9 (21%) clindamycin-amikacin-treated patients (P = 0.19; not significant). The rates of bacteremia were 2 and 4%, respectively. The rates of bronchopneumonia were 14.3 and 23.2%, respectively (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…Short antibiotic prophylaxis reduces the risk of drug side effects and the risk of colonization and superinfection due to resistant pathogens. However, in major head and neck cancer surgery there is no consensus concerning antibiotic prophylaxis policy [6,11,12,17,19,24,25,28,34]. In the present study, an amoxicillin and clavulanic acid regimen failed to prevent WI in 50% of patients.…”
Section: Discussioncontrasting
confidence: 73%
“…Short antibiotic prophylaxis reduces the risk of drug side effects and the risk of colonization and superinfection due to resistant pathogens. However, in major head and neck cancer surgery there is no consensus concerning antibiotic prophylaxis policy [6,11,12,17,19,24,25,28,34]. In the present study, an amoxicillin and clavulanic acid regimen failed to prevent WI in 50% of patients.…”
Section: Discussioncontrasting
confidence: 73%
“…Many different systemic regimens have been reported in the setting of postoperative antimicrobial coverage: clindamycin plus aminoglycoside, cephalosporin monotherapy, and b-lactam/b-lactamase inhibitor. 5 One study also suggested to use antimicrobials that are resistant to b-lactamases, as many gram-negative bacteria possess these enzymes. 23 Additionally, studies that utilized topical antimicrobials preoperatively to decolonize the surgical area have not been shown to be beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infections after general head and neck cancer surgery have an incidence rate of 8% to 45% with standard surgical infection prophylaxis, [1][2][3][4][5][6][7][8][9][10][11] but can be seen in up to 87% without surgical infection prophylaxis. 2,7,8,[12][13][14] Few studies have examined patients undergoing clean or cleancontaminated microvascular reconstruction for head and neck cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The reported rates of surgical site infection in head and neck free flap surgery range from 8.1% to 41% . The risk of surgical site infection after head and neck reconstruction is postulated to be higher than other anatomic sites because of the creation of communication between the aerodigestive tract and neck, contamination with saliva and respiratory secretions, and postoperative tissue dead space .…”
Section: Introductionmentioning
confidence: 99%